Pengembangan Konsep Teknologi Hijau Dalam Agroindustri Minyak Goreng - Siswahyu, Agung; Widyantoro, Murwan (Jurnal Jaring SainTek, 2025)
This study evaluates the utility and emission reductions of a 1,500 ton/day palm cooking oil production plant through Aspen Hysys simulations (gate-to-gate) and process scenarios. The model includes degumming, bleaching, deodorization, fractionation, hot oil heating utilities, water cooling, and electricity. Three scenarios were tested: (1) Heat Exchanger Networking (HEN) for inter-stream heat exchange; (2) oil recovery in spent bleaching earth (SBE) as fuel; and (3) integration of HEN + SBE recovery. Results show reductions in heat, water, electricity, fuel, and emission requirements compared to the baseline, with the best performance differing per metric: scenario 3 effectively reduces heat, fuel, and emission requirements, while scenario 2 is efficient for water and electricity consumption. The study confirms that the application of green technology improves both the efficiency and sustainability of the Indonesian cooking oil industry.